2007
DOI: 10.1227/01.neu.0000255388.03088.b7
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Transforaminal Lumbar Interbody Fusion for the Treatment of Degenerative Lumbar Instability

Abstract: pTLIF allows for safe and efficient minimally invasive treatment of single and multilevel degenerative lumbar instability with good clinical results. Further prospective studies investigating long-term functional results are required to assess the definitive merits of percutaneous instrumentation of the lumbar spine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
157
2
4

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 141 publications
(173 citation statements)
references
References 14 publications
9
157
2
4
Order By: Relevance
“…Symptomatic misplaced pedicle screws (2%) and cage migration (2%) were also reported. Our complication and reoperation rates appear comparable to other results of minimally invasive transforaminal lumbar interbody fusion [3,4,6,8,14,16,19,[22][23][24][25]. In the series of Rouben et al [22], the overall rate for repeat surgery (14.2%) was higher than ours.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Symptomatic misplaced pedicle screws (2%) and cage migration (2%) were also reported. Our complication and reoperation rates appear comparable to other results of minimally invasive transforaminal lumbar interbody fusion [3,4,6,8,14,16,19,[22][23][24][25]. In the series of Rouben et al [22], the overall rate for repeat surgery (14.2%) was higher than ours.…”
Section: Discussionsupporting
confidence: 86%
“…Multiple studies have reported favorable results after treatment of spondylolisthesis and other degenerative lumbar diseases with minimally invasive transforaminal lumbar interbody fusion [3,4,6,8,16,17,[20][21][22][23][24][25]. These studies described results from 6 to 49 months after surgery; however, to our knowledge, data at minimum 5-year followup have never been reported.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Four studies were removed because they included the same, or a subset of the patient population of their previous studies [16][17][18][19]. One study analyzed three groups of patients (divided by the number of operative levels) [12]. We only included the single level group because the patient's number of multilevel fusion procedures was not large enough to meet our inclusion criteria.…”
Section: Resultsmentioning
confidence: 99%
“…However, only limited Class I evidence is available [4,[6][7][8][9][10][11][12][13][14][15][16][17][18][19]. The objective of the present study was to provide cumulative effect estimates of the clinical and radiological outcomes using meta-analysis and to determine which surgical technique was more beneficial.…”
Section: Introductionmentioning
confidence: 99%